2015
DOI: 10.1111/andr.12116
|View full text |Cite
|
Sign up to set email alerts
|

Anti‐Müllerian hormone, a Sertoli cell‐derived marker, is decreased in plasma of male patients in all stages of chronic kidney disease

Abstract: SUMMARYMale patients with terminal renal failure are often infertile and exhibit an abnormal sex hormone pattern in plasma. We studied patients in all chronic kidney disease (CKD) stages to determine plasma levels of anti-M€ ullerian hormone (AMH), a Sertoli cellderived marker, and other sex hormones. Seventy-eight male patients with CKD stages 1-5 and a median age of 40 years (22-50 years), as well as 20 healthy controls with a median age of 37 years (26-44 years), were enrolled. The CKD patients were evenly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
9
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 29 publications
4
9
1
Order By: Relevance
“…Previous explanations include disturbances in the hypothalamic-pituitary-gonadal axis resulting in altered levels of luteinizing hormone, follicle-stimulating hormone, and testosterone. Our findings in this and previous studies [6, 7] show that the absolute change in plasma AMH and miR-155 levels were greater than those of testosterone. Successful renal transplantation has been shown to normalize testosterone deficiency in uremic men [29].…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…Previous explanations include disturbances in the hypothalamic-pituitary-gonadal axis resulting in altered levels of luteinizing hormone, follicle-stimulating hormone, and testosterone. Our findings in this and previous studies [6, 7] show that the absolute change in plasma AMH and miR-155 levels were greater than those of testosterone. Successful renal transplantation has been shown to normalize testosterone deficiency in uremic men [29].…”
Section: Discussionsupporting
confidence: 76%
“…We found no association between miR-155 and CRP in this CKD population, indicating that the elevated miR-155 levels were a response to a mechanism other than inflammation associated with CRP as a cause of impaired semen quality. We have recently reported major decreases in plasma levels of AMH, a marker of Sertoli cell function, in men with CKD [6, 7]. To evaluate this in relation to fertility, we included assay of AMH levels in this study, and found an association between low AMH levels and a low percentage of motile sperm cells in the entire study population.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…This is consistent with Eckersten, Giwercman, Bruun, et al. () who showed for the first time that plasma AMH level was decreased in dialysis patients and in men with mild and moderate renal dysfunction. However, the authors did not find a cause for the decreased AMH level, but they speculated on the effects of inflammation, uraemic toxicity or other causes.…”
Section: Discussionsupporting
confidence: 92%
“…In CKD, Eckersten, Giwercman, Bruun, and Christensson () reported that the mean plasma AMH level in stages 1–4 was lower than that in controls and represented a decrease by 30%. Furthermore, AMH level was found to be greatly decreased in male patients with ESRD which may reflect SC impairment in those patients (Eckersten, Giwercman, & Christensson, ).…”
Section: Introductionmentioning
confidence: 99%